Antipsychotic Treatment Failure: A Systematic Review on Risk Factors and Interventions for Treatment Adherence in Psychosis - El Abdellati, Kawtar; De Picker, Livia; Morrens, Manuel (Frontiers in Neuroscience, 2020)
Objective: Antipsychotic medication nonadherence has detrimental effects on patients’ clinical outcome. It is unclear which risk factors affect adherence most and which interventions are effective at improving adherence to antipsychotic medication. The aim of this systematic review is to summarize evidence exploring risk factors of nonadherence to antipsychotic treatment and effectiveness of intervention to improve adherence in patients with psychotic spectrum disorders. Methods: We conducted a systematic search in Pubmed from 1994 to 2019 using a structured search strategy. Studies were quality assessed, and studies reporting on possible risk factors and intervention strategies were synthesized. Results: We reviewed 26 studies on factors related to antipsychotic medication adherence and 17 studies on interventions to improve adherence in patients with psychosis spectrum disorders. Risk factors of nonadherence included younger age, poor illness insight, cannabis abuse and the presence of severe positive symptoms. Antipsychotic medication adherence was associated with positive attitude towards medication of both patients and their family, family involvement and illness insight. Somewhat consistent evidence was found for interventions involving family, technology-based interventions and strategies combing depot-medication with psychoeducation. However, given the wide range of heterogeneous interventions and methodological limitations, findings must be interpreted with caution. Conclusion: Despite much effort invested in the research area of antipsychotic medication adherence, the heterogeneity in study design and outcome, adding to confounding effects and possible biases, and methodological restraints complicate comparability of the results. Future research in this field should therefore be conducted on patient-tailored interventions, considering risk factors affecting the patient and implementing well-validated, standardized assessment methods. Accordingly, this systematic review seeks to facilitate endeavors improving adherence to antipsychotic treatment, by identifying modifiable and non-modifiable risk factors, outlining effective intervention strategies, and proposing recommendations to enhance adherence strategies.